NEUROEDUCATION: MOZART EFFECT ON SIGNIFICANT LEARNING IN INSTITUTIONS OF HIGHER EDUCATION - Paredes Padilla, Lady Nataly; Vasco Vasco, Jorge Antonio; Soto Ayala, María Fernanda; Rodríguez Ulcuango, Olga Maritza (mktDESCUBRE; Vol 1 No 3 (2020): Special Edition 1st International Marketing Congress, 2020)
Within the teaching and learning system auditory neuromarketing is not considered because there is an erroneous ideology that this type of tools It is used only to influence the purchase decisions of customers or consumers, what most people do not know is that neuromarketing can have different applications in different areas such as education to potentiate meaningful learning in level students higher. In the Neuroeducación the Mozart Effect has been considered as an auditory stimulus that improves the level of attention of the students, this being the objective of the research, the study is considered with the deductive method and through a biometric equipment known as electroencephalogram in which the experimentation managed to analyze the reaction of the brain to an auditory stimulus in this case Mozart’s music that was applied during the interpretation of the mathematics exam, this effect was applied for 15 minutes, Also after the exam, a survey was applied to analyze the impact it had on the students, giving as a result that most of them felt relaxed and concentrated when listening to Mozart’s music.